2009
DOI: 10.1093/jb/mvp010
|View full text |Cite
|
Sign up to set email alerts
|

Serine Racemase with Catalytically Active Lysinoalanyl Residue*

Abstract: Serine racemase synthesizes d-serine, a physiological agonist of the NMDA receptor in mammalian brains. Schizosaccharomyces pombe produces serine racemase (spSR) that is highly similar to the brain enzyme. Our mass-spectrometric and X-ray studies revealed that spSR is modified with its natural substrate serine. spSR remains partially active even though its essential Lys57 inherently forming a Schiff base with the coenzyme pyridoxal 5'-phosphate is converted to N(6)-(R-2-amino-2-carboxyethyl)-l-lysyl (lysino-d-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…The only available experimentally determined structures of a eukaryotic serine racemase are four crystal structures of SR from fission yeast, S. pombe (PDB accession codes 2ZR8, 2ZPU, 1WTC, and 1V71) 14,16 . Like hSR, S. pombe SR acts as both a racemase and an eliminase and is activated by divalent cations and ATP.…”
Section: Multiple Alignment Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The only available experimentally determined structures of a eukaryotic serine racemase are four crystal structures of SR from fission yeast, S. pombe (PDB accession codes 2ZR8, 2ZPU, 1WTC, and 1V71) 14,16 . Like hSR, S. pombe SR acts as both a racemase and an eliminase and is activated by divalent cations and ATP.…”
Section: Multiple Alignment Analysismentioning
confidence: 99%
“…While the structure of a SR orthologue from the fission yeast Schizosaccharomyces pombe (35.1% 14 or 40% 15 sequence identity to human SR) has been solved 14,16 , the structure of a mammalian SR orthologue remains elusive. We therefore set out to establish a strategy for the generation and screening of human SR mutants in hopes of gaining insight into the structure-function relationships within the enzyme.…”
mentioning
confidence: 99%
“…Docking studies were carried out for the compounds 4-8 to verify whether they could be accommodated in the SR binding pocket. Crystal structures of SR have been recently solved [20][21][22] and the comparison between the holo SR structures and those in the presence of malonate revealed that the binding of the inhibitor triggers a transition from an open to a closed conformation. For this reason, in a previous work by us, SR conformational flexibility was investigated, identifying a few intermediate conformations that were included in our docking studies together with the open and closed conformations 33 .…”
Section: Resultsmentioning
confidence: 99%
“…In cells transfected with SR the pyruvate/D-serine ratio was found to be around 4, thus indicating that the a,b-elimination reaction might play a physiological role in the control of D-serine concentration 15 . Crystal structures of eukaryotic SR were solved from different sources, human, rat 20 and Schizosaccharomyces Pombe 21,22 , in holo form or in complex with the inhibitor malonate ( Figure 1). Despite the availability of structural data and the identification of a few inhibitors [23][24][25][26] , the development of specific and more potent SR inhibitors remains very challenging 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, among the ing that it is biosynthesized in C. elegans. In fact, Ser racemase (EC 5.1.1.16), a synthetic enzyme that produces D-Ser from L-Ser, has been found in various organisms, including yeast Schizosaccharomyces pombe, plants, and mammals (19,69,73). Moreover, in the C. elegans database WormBase (http://www.wormbase.org/), the gene T01H8.2 is annotated as encoding a putative Ser racemase.…”
Section: Discussionmentioning
confidence: 99%